Research on manufacturing dry mixed cement mortar with high compressive strength, high flexural strength, low shrinkage and high watertightness for restoration of damaged hydraulic structures in Vietnam - Phu, Nguyen Quang; Uyen, Hoang Pho; Hua, Jiang Lin; Jiaping, Liu (Vietnam Journal of Mechanics, 2008)
Using normal materials to manufacture the mixed mortar is necessary for restoration of hydraulic structures in Vietnam. It will salvage the materials and decreases the cost price of the mortar. In this research, we used cement made in Vietnam (Chinfon - Haiphong cement), natural sand (Lo River sand), polymer acrylic and high range water reducing (of SIKA company)’ with proportion 1 : 3 : 0.03 : 0.003 by weight. The water to cement ratio is 0.5, which always ensure the compressive strength of mortar more than 40 MPa and small shrinkage, good watertightness, and high adhesion. That is suitable for the restoration of concrete structures in general and hydraulic structures in particular of Vietnam. The dry mixed mortar is manufactured and in bag of 15±0.5 kg weight